Implementasi Pemberatan Pidana pada Pelaku Pelecehan Seksual Anak dalam Putusan Pengadilan di Indonesia - Sulistyanta Sulistyanta; Diana Lukita Sari; Fabyan Rayyan Aqila (Indonesian Publication Center, 2026)
This study aims to analyze the implementation of increased sentencing for recidivists in child sexual abuse crimes in Indonesia and examine the construction of judges' considerations in court decisions. The problem arises because, although laws and regulations regulate increased sentencing for recidivists, inconsistencies in sentencing practice persist. This study uses a normative juridical method with a statutory and conceptual approach. The primary legal materials consist of laws and court decisions, while secondary legal materials are obtained from legal literature and journals. The results indicate that while the regulation of increased sentencing for recidivists is normatively regulated in the Criminal Code and the Child Protection Law, its implementation is not entirely consistent. Judges' considerations are often influenced by subjective factors such as the perpetrator's remorse and social background, resulting in disparities in sentencing. Therefore, stricter sentencing guidelines are needed to ensure legal certainty, justice, and maximum protection for child victims.